Qualitative Comparative Analysis and the Study of Policy Processes. Issue 4 (8th August 2017) - Fischer, Manuel; Maggetti, Martino
Abstract: Given the increasing popularity of Qualitative Comparative Analysis (QCA) for the study of public policy and policy processes, this article offers a review of two key issues: multiple configurational causality and temporality. On the one hand, the study of multiple configurational causal relations allows researchers to deal with the extremely complex set of elements that interact in policy processes. However, this task poses the challenge of balancing deductive and inductive logics in a research design. On the other hand, policy process theories often involve temporal arguments, but QCA does not easily deal with dynamic elements. This article discusses these challenges and proposes several ways to address them. It thereby illustrates the advantages and limitations of QCA for students of policy processes.